Pengaruh Service Exellent Dan Harga Dalam Menciptakan Kepuasan Pelanggan Pada PT. Wahana Trans Lestari Medan - Winda Bella Syafira; Tika Nirmalasari (Jurnal Bintang Manajemen, 2023)
This study aims to determine the effect of Excellent Service and Price in Creating Customer Satisfaction at PT. Medan Trans Lestari rides. The type of data analysis used in this research is to use quantitative data analysis techniques which only use numerical calculations and then draw conclusions. The testing technique carried out in this study uses descriptive statistical tests, classical assumption tests, hypotheses then multiple regression tests and finally the coefficient of determination test. In this study using statistical software SPSS Version 25. The results of this study are based on the results of the t test test which can be seen in the table above, the hypothesis test criteria are accepted, namely H1 is accepted, which means that partially Service Excellent has a positive and significant influence on customer satisfaction. Based on the results of the t test, it can be seen that, partially, it can be concluded that H2 is rejected, which means that partially, price does not have a positive and significant effect on customer satisfaction. Then simultaneously the variables Service Excellent (X1) and Price (X2) together have a positive and significant effect on Customer Satisfaction of PT. Trans Lestari rides.